Morfologia strategii zasobowych : Egzemplifikacje - Krupski, Rafał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents the methods of resource strategy structuralization. The author's own research confirms that relational resources and employee attitudes contribute to a competitive advantage. Consequently, the proposals of relational resource strategy structuralization in a deductive proceedings and the strategies of employee loyalty creation (as the example of attitudes creation strategy) in a inductive proceedings were presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 185-191